COMPARISON OF NEPAFENAC PLUS STEROID VERSUS STEROID ALONE FOR CONTROL OF OCULAR INFLAMMATION AFTER PHACOEMULSIFICATION - Dr Manpreet kour; Dr. Nancy Sharma; Dr Malvika Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Introduction: Cataract is the most common surgical procedure. Study was done to compare the effect of nepafenac 0.1% plus prednisolone 1% vs prednisolone 1% alone in controlling ocular inflammation after phacoemulsification Material and Methods: A total of 140 patients were randomized to receive prednisolone 1% (group I) vs nepafenac plus prednisolone 1% (group II) after uneventful phacoemulsification. Patients were examined on first day, one week and one month for vision, slit lamp evaluation for anterior segment inflammation and cystoid macular edema. Results: Average visual acuity was 6/9 in both groups. Anterior segment inflammation was significantly less in group II on first post operative day. On later visits, there was no significant difference in inflammation in both groups. CME was not seen in any group. Conclusion: This study suggests that addition of nepafenac 0.1% to prednisolone 1% significantly reduces the intraocular inflammation after phacoemulsification in the early postoperative period.